(3GdeGdjI GdYGeI aj GdfXQjI hGdJWHjb (B/s - (3ehSLQja, QjJTGQOs; (3ehSLQja, HjLj s ((3GdQjGV(B: s (3OGQ GdeQjN ddfTQ(B, s, 1992)
(3GdhXGFa GdeGdjI, fXQjI GdSdY GdELJeGYjI GdYGeI, GdSdY GdELJeGYjI, fXQjI GdJhRjY GdCeKd, GdENJjGQ GdYGe hJSjjS GdeGdjI, eHGOF Jbhje GdCfaGb, Jbhje GdCfaGb, OQGSI MGdGJ ebOeI aj GdVQjHI, efGgL GdYOGdI GdVQjHjI, YHA GdVQjHI hGdCfaGb, eHGOF GdYHA GdVQjHj, ebOeI aj GdESJbQGQ, GdfGJL hGdYeGdI hGdJVNe, JLQHI GdSjGSI GdeGdjI, GdeGdjI GdYGeI aj GdOhd GdfGejIs
Keywords: (3GdeGdjI GdYGeIs